Assessing the Approach to a Thrombosed AV Graft. Issue 5 (5th February 2014) - Ponce, Pedro; Carvalho, Telmo; Messias, Humberto; Neves, Fernando; the Lisbon VAC Interventional Nephrology Team
Abstract The patency of the vascular access (VA) is a fight for the attending nephrologist. A retrospective observational study was conducted to compare the success rate of surgical versus endovascular technique percutaneous transluminal angioplasty (PTA) for graft thrombosis treatment. Of 3008 patients, 22.1% patients were dialyzed through grafts. Forty‐five percent of all prevalent patients referred due to VA malfunction had a graft. For 18 months, 336 thrombosed grafts were submitted to surgery in 228 cases and to PTA in 126. PTA for thrombolysis included the Pharmaco‐Mechanical Technique and the Arrow‐Trerotola Device. Procedures were performed as outpatient, with an average delay of 1 day. Immediate success was 100% for surgery and 87.3% for PTA. The unassisted patency for thrombosed grafts for surgery/PTAwas 265.12 ± 15.30/230.59 ± 19.83 days respectively, favoring surgery. The primary patency for thrombosed grafts treated by surgery/PTA at 30, 90, and 180 days was, respectively, 74.1%/81%, 63.2%/67.5%, and 53.9%/55.6% all in favor of PTA. AV grafts have a much higher rate of thrombosis than fistulas. Graft thrombosis can be dealt either by surgery or PTA, with identical success.